Basic Training Management in Improving the Quality of Candidates for Civil Servants (Cpns) At the Ministry of Health - Bastaman, Rudi; Trisnamansyah, Sutaryat; Wasliman, Iim; Sauri, Supyan (International Journal of Science, Technology & Management, 2022)
The background of this study is still the occurrence of violations of the code of professional ethics of Health civil servants and the lack of quality of health services and behavior of Health civil servants in providing health services to the community. This research is based on the concept and theory of POAC management according to Terry which consists of planning, organizing, implementation and supervision. The general purpose of the study is to review and analyze Basic Training Management in improving the quality of CPNS in the Ministry of Health, specifically to obtain an overview of planning, implementation, supervision, evaluation, inhibiting factors and efforts to overcome obstacles in training. This study uses descriptive method with qualitative approach according to the facts through observation techniques, interviews, and documentation studies on CPNS basic training in Health Training Center Ciloto. The results showed that: (1) training planning is in accordance with planning theory and training policy standards but there are still limitations in the number of certified teaching resources. (2) the implementation is in accordance with the implementation theory and training program standards but there are still weaknesses of some teachers in terms of online teaching strategies. (3) supervision is in accordance with supervision theory and supervision quality standards but the supervisor has not been fully involved in the entire learning process. (4) The evaluation is in accordance with the evaluation theory and evaluation standards of the assessment instrument but does not involve all related elements in the evaluation of graduation. (5) the inhibiting factors of training include the limited number of certified teachers, the weakness of some teachers in online teaching strategies, learning is not on schedule due to internet network connection constraints, supervisors have not been fully involved in all training agendas, and the evaluation has not involved all related elements. (6) the efforts that have been made include cooperation between training agencies, improvement of teacher competence, improvement of internet capacity, communication and coordination related to policy supervision and evaluation of comprehensive training. Management basic training in improving the quality of Health employess has been carried out according to the concept and theory of management, but there are still limitations in terms of the number of certified teachers, teacher competence, supervision and evaluation.